Association Between Sarcopenia and Acupressure Testing in Older Adults Requiring Long-Term Care - Takahiro Shiba; Yohei Sawaya; Ryo Sato; Tamaki Hirose; Lu Yin; Masataka Shiraki; Masahiro Ishizaka; Akira Kubo; Tomohiko Urano (Medicina)
Background and Objectives: This study analyzed the relationship between pressure pain test outcomes and sarcopenia in elderly patients and explored possible clinical applications. Materials and Methods: The participants included 143 older adults requiring long-term care who could be diagnosed with sarcopenia. Along with sarcopenia diagnosis, the participants underwent acupressure testing symmetrically at nine sites (occiput, lower cervical, trapezius, supraspinatus, second rib, lateral epicondyle, gluteus, greater trochanter, and knee), totaling 18 sites. The analyses included comparisons of sarcopenia status and total tender points between the groups and a multivariable analysis. The association between sarcopenia and the number of tender points were examined based on correlations between the number of tender points and grip strength, walking speed, and skeletal muscle mass index (SMI). Intergroup comparisons and multivariable analysis of tender points with and without sarcopenia were performed to investigate specific tender points associated with sarcopenia. Results: An independent association was observed between sarcopenia and the number of tender points (p = 0.001). Furthermore, the number of tender points was correlated with grip strength (ρ = −0.536, p < 0.001), walking speed (ρ = −0.200, p = 0.028), and SMI (ρ = −0.394, p < 0.001). The supraspinatus (p = 0.029, 95% confidence interval: 1.221–35.573) and lower cervical (p = 0.039, 95% confidence interval: 1.050–7.245) regions were identified as specific tender points. Conclusions: In older adult patients requiring long-term care, sarcopenia is associated with an increased number of tender points throughout the body, with the supraspinatus and lower cervical regions potentially being specific tender points. Acupressure testing for tenderness may be a useful assessment parameter in sarcopenia patients.